Investigation into the H–D kinetic isotope effect (KIE) on the humidity sensing characteristics of YSZ; Journal of Materials Science: Materials in Electronics; Vol. 37 - Ibragim Makhmud A. M. A. Akhmed Mustafa Akhmed; Esawii H. A. Heba; Mezentseva Zh. V.; Doroshkevich O. S. Oleksandr Sergiyovich; Laptev R. S. Roman Sergeevich (2026, 2026)
Title screen